The critical success factors (CSFs) for IT projects - Gheni, Ali Yahya; Jusoh, Yusmadi Yah; A. Jabar, Marzanah; Mohd Ali, Norhayati (Faculty of Electronic and Computer Engineering, Universiti Teknikal Malaysia Melaka, 2017)
Huge yearly investments were made by organizations for the development and maintenance. However, it has been reported that most of the IT projects fails as it is delayed, over budget and discontinued quality. A systematic literature review (SLR) was conducted to identify the critical success factors (CSFs) for the IT projects. Nine (9) CSFs was identified from the SLR. An online survey was conducted among 103 respondents from developers and IT managers. The data was analyzed using the Statistical Package for Social Science (SPSS 22). The findings showed that the highest CSFs of IT projects is commitment and motivation. Project monitoring was found the lowest score ranked by respondents.